2013
DOI: 10.4236/aid.2013.34043
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of HIV-Infected Patients on Antiretroviral Therapy in a Large Public Cohort in West Africa, Burkina Faso: Frequency and Associated Factors

Abstract: Background: In sub Saharan Africa, small size surveys have demonstrated early high mortality among infected patients on antiretroviral therapies (ART). Few studies have been conducted in large cohorts of HIV-patients in public health care system in West Africa. Objectives: Our study aims to determine mortality rate and its predictors in a cohort of patients on ART in a public daycare hospital in Burkina Faso. Methods: We have carried out a retrospective cohort study. All HIV-infected patients on ART between Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 40 publications
3
6
1
Order By: Relevance
“…This result is in agreement with the study done in Burkina Faso [4]. However, this finding was low compared to common rates in resources-limited countries [5] and higher compared to 2.03/100 persons-years in the Eastern Ethiopia and 1.89/100 persons-years in Western Ethiopia respectively [6, 7].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result is in agreement with the study done in Burkina Faso [4]. However, this finding was low compared to common rates in resources-limited countries [5] and higher compared to 2.03/100 persons-years in the Eastern Ethiopia and 1.89/100 persons-years in Western Ethiopia respectively [6, 7].…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with studies [4, 6, 12, 20, 25, 27]. Studies have substantiated the fact that low CD4 cell count, a marker of advanced immunodeficiency, was associated with opportunistic infection thereby increasing the likelihood of death [28].…”
Section: Discussionsupporting
confidence: 91%
“…The knowledge of these factors responsible for mortality among PLHIV can guide the policy makers to address them, suggesting and implementing remedial measures through the program. The mortality rate in our study cohort was 14.4%, which was higher than in similar studies conducted in Africa [9][10][11], which is probably due to the higher number of deceased patients in WHO stage 3/4 of the disease in our study.…”
Section: Discussioncontrasting
confidence: 53%
“…Studies from the Sub-Saharan African region have observed a similar trend, with respect to the role of nutrition in PLHIV. Low BMI was associated with mortality in studies from Burkino Faso [9,14], northern Ethiopia [10] and Nigeria [11], where, as in studies from Tanzania [6] and Ethiopia [15], history of significant weight loss, and weight less than 45 kg were predictors of mortality. Poor nutritional status at the initiation of ART and its deterioration within the first 3 months of starting therapy was an important predictor of mortality in another study from Tanzania [16].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation